Air retaining grids—a novel technology to maintain stable air layers under water for drag reduction. (10th June 2019) - Mail, M.; Moosmann, M.; Häger, P.; Barthlott, W.
Abstract : Extreme water repellent 'superhydrophobic' surfaces evolved in plants and animals about 450 Ma: a combination of hydrophobic chemistry and hierarchical structuring causes contact angles of greater than 150°. Technical biomimetic applications and technologies for water repellency, self-cleaning (Lotus Effect) and drag reduction (Salvinia Effect) have become increasingly important in the last two decades. Drag reduction (e.g. for ship hulls) requires the presence of a rather thick and persistent air layer under water. All existing technical solutions are based on fragile elastic hairs, micro-pillars or other solitary structures, preferably with undercuts (Salvinia Effect). We propose and provide experimental data for a novel alternative technology to trap persistent air layers by superhydrophobic grids or meshes superimposed to the solid surface: AirGrids. AirGrids provide a simple and stable solution to generate air trapping surfaces for drag reduction under water as demonstrated by first prototypes. Different architectural solutions, including possible recovery techniques for the air layer under hydrodynamic conditions, are discussed. The most promising target backed by first results is the combination of Air Retaining Grids with the existing microbubble technology. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 2)'.